Takaful and Retakaful Principles, Practices and Challenges - Issa Khan (Penerbit UTHM, 2023)
This book provided an introduction to takaful, its pitfalls, key contracts, and an overview of takaful in several Muslim countries. The book detailed the various takaful business structures and how they are governed under Shari’ah law. This book also examined the views of prominent Islamic finance regulators like the Accounting and Auditing Organisation for Islamic Financial Institutions (AAOIFI) and the Central Bank of Malaysia to provide definitive answers to contentious questions about Takaful. The effects of the Covid-19, or bird flu, pandemic on the takaful sector were also evaluated, and solutions were provided. This book discussed the environmental, economic, and social sustainability of takaful. Types of retakaful, Shari’ah considerations, and operational and model retakaful are discussed in this book. Finally, various solutions to the problems and difficulties of retakaful have been proposed.